Sosialisasi Pengelolaan Sampah Menjadi Rupiah Menuju Lingkungan Bersih dan Sejahtera di Dusun Krajan B, Desa Wonorejo Jember - Girinda Decalzgi Azade; Inge Wiliandani Setya Putri; Arik Aguk Wardoyo; Dinara Safira; Adinda Margaretha Natara; Alfarabi Putra Ramadhan Wijaya; Ridhotul Noval; Muhammad Syariifuddiin Allaam Sugiharto; Riza Achmad (Assoeltan: Indonesian Journal of Community Research and Engagement, 2024)
Waste management is a major challenge in various regions, including in Krajan B Hamlet, Wonorejo Village, Kencong District. The waste management socialization program is one of the efforts to reduce the amount of waste produced and increase public awareness of the importance of waste management. This community service program aims to help the community in converting waste into economic value that is beneficial to the surrounding community. This community service method uses Participatory Rural Appraisal (PRA). The results of community service show that this waste management socialization has succeeded in making waste a source of additional income for residents which can ultimately create a cleaner and healthier environment. The impact of this community service is expected to change people's attitudes towards waste, reduce pollution, and improve the economic welfare of the community there. Thus, this program is expected to be an example for other regions in creating a cleaner, healthier, more economical environment, and building a more independent and prosperous advanced society.